1998
DOI: 10.1029/98ja00762
|View full text |Cite
|
Sign up to set email alerts
|

An overview of the early November 1993 geomagnetic storm

Abstract: Abstract. This paper describes the development of a major space storm during November 2-11, 1993. We discuss the history of the contributing high-speed stream, the powerful combination of solar wind transients and a corotating interaction region which initiated the storm, the high-speed flow which prolonged the storm and the near-Earth manifestations of the storm. The 8-day storm period was unusually long; the result of a high-speed stream (maximum speed 800 km/s) emanating from a distended coronal hole. Storm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
65
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 97 publications
6
65
1
Order By: Relevance
“…Toroidal mode power is distributed fairly equally between the dawn and dusk flanks of the magnetosphere inside L = 8, with greater probability of occurrence at higher L-values. The former result differs from AMPTE CCE and AMPTE IRM satellite studies at higher L-values at solar minimum (Anderson et al, 1990;Lessard et al, 1999;Takahashi et al, 2002), but is consistent with a recent analysis of a six month interval of GOES 6 geosynchronous data in 1993, a period characterized by 27-day recurring high speed solar wind streams characteristic of the declining phase of the solar cycle (Knipp et al, 1998). The occurence of Pc-5 oscillations has been correlated with high speed solar wind periods O'Brien et al, 2001), providing some support for the Kelvin-Helmholtz theory of toroidal mode FLR excitation.…”
Section: Discussioncontrasting
confidence: 28%
“…Toroidal mode power is distributed fairly equally between the dawn and dusk flanks of the magnetosphere inside L = 8, with greater probability of occurrence at higher L-values. The former result differs from AMPTE CCE and AMPTE IRM satellite studies at higher L-values at solar minimum (Anderson et al, 1990;Lessard et al, 1999;Takahashi et al, 2002), but is consistent with a recent analysis of a six month interval of GOES 6 geosynchronous data in 1993, a period characterized by 27-day recurring high speed solar wind streams characteristic of the declining phase of the solar cycle (Knipp et al, 1998). The occurence of Pc-5 oscillations has been correlated with high speed solar wind periods O'Brien et al, 2001), providing some support for the Kelvin-Helmholtz theory of toroidal mode FLR excitation.…”
Section: Discussioncontrasting
confidence: 28%
“…They did not estimate the energy lost to plasmoids streaming down the magnetotail. Knipp et al [1998] analyzed the November 1993 storm, which was a hybrid event where a high-speed stream followed a CME. They found that high-speed streams could be enormously geoeffective, and for this extreme event the ionospheric heating was ∼190 × 10 15 J, with 30% of that generated within 24 hours of storm onset.…”
Section: Previous Workmentioning
confidence: 99%
“…Over many years of research into the effects of solar wind forcing on the ionosphere-thermosphere (IT) system, it has been generally assumed that energy enters and dissipates in the auroral zones and ring current (Akasofu 1981;Weiss et al 1992; Knipp et al 1998;Li et al 2012, and references therein). This assumption is based on the effect of particle precipitation which gives rise to intense auroral emissions and high conductivity in the auroral zone (Evans et al 1977;Vondrak & Robinson 1985;Fuller-Rowell & Evans 1987;Coumans et al 2004, and many others).…”
Section: Introductionmentioning
confidence: 99%